(3aJM GdhgGH TQM efgL GdWdGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s ((3eMeO GdbGVjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi CaVGdg hGdUdGI hGdSdGe Ydi SjOfG eMeO hUMHg hBdg hHYO abO cfJ GNJUQJ efgGL GdWGdHjf aj Gdabg JCdja TjN GdESdGe CHj RcQjG jMji eMjj GdOjf Gdfhhj QMeg Gddgs
(3BNQgG (B:s
(3hMda edJRe CfcQ TQWYd ChQO ajUOb dCf GdCUd YOeg aEf GNJdaG HYO GdGSJMbGb aj bOQYd Cj bOQ eQOhO JMGdaG hddYGed CLQI GdeKd ceG Yde ef HGd GdGNJdGa aj cjajI GdYbO hcJGH GdbQGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3cTa GdXfhf (B2 / 1875s
(3TPQGJ GdPgH (B8 / 134s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs